2020
DOI: 10.1007/s42452-020-3114-4
|View full text |Cite
|
Sign up to set email alerts
|

CO/CO2 adsorption and sensing on borophene

Abstract: In this paper, the absorption of CO and CO 2 molecules on the two-dimensional structure of borophene has been investigated. Theoretical calculations based on density functional theory shows that the absorption energy of CO and CO 2 molecules on borophene are much higher than that of graphene. Also, by lithium decorated borophene, the absorption energy is increased. So, it can be used as a toxic sensor of CO and CO 2 gases. The monolayer borophene and borophene decorated with lithium is still conductive after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…When C and O atoms are adsorbed by borophene nanosheets, a charge transfer mechanism between CO and borophene occurs, C and O atoms gain electrons and therefore borophene nanosheets lose electrons. Therefore, CO gas is a charge acceptor when faced with borophene [58][59][60]. In this regard, adsorption of CO molecules on borophene has increased the electrical resistance of borophene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When C and O atoms are adsorbed by borophene nanosheets, a charge transfer mechanism between CO and borophene occurs, C and O atoms gain electrons and therefore borophene nanosheets lose electrons. Therefore, CO gas is a charge acceptor when faced with borophene [58][59][60]. In this regard, adsorption of CO molecules on borophene has increased the electrical resistance of borophene.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al [55] investigated the effect of graphene dispersion on NH 3 gas sensing characteristics of polyaniline gas sensor. The sensor Although there have been inspired theoritical studies about the adsorption of CO molecules to the borophene surface [58][59][60] in the last two years, there are no experiment reports. Also, there have been only a few reports on the detection of NH 3 gas using borophene based sensors over the last four years [61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…These gases are very hazardous for human health and to resolve these concerns, nanodevices based upon the sensing of these gases are of great importance in the clinical analysis. 163 In another study, sensing of highly toxic gases including phosgene (COCl 2 ) and CO has been demonstrated with the help of highly anisotropic borophene. Results showed that the adsorption of COCl 2 is more favorable than that of CO and established the role of borophene in potential biosensing.…”
Section: Borophene-enabled Efficient Biosensing For Disease Diagnosticsmentioning
confidence: 99%
“…In its different forms, boron, a naturally occurring element of earth, has been shown to have promising CO and CO 2 adsorption capability [17][18][19]. Studies have also proven the adsorption capabilities of borophene [20][21][22] and deem it a promising agent for energy, sensor, and biomedical applications based on its properties [23,24].…”
Section: Introductionmentioning
confidence: 99%